A Case of Solitary Angiokeratoma - Coşkun, Başak K.; Ataseven, Arzu; Saral, Yunus; Öztürk, Perihan; Akpolat, Nusret (Fırat University, 2005)
Angiokeratomas are vascular lesions which developed from dilated blood vessels lying subepidermal and showing an epidermal proliferative reaction. Although angiokeratomas are benign lesions especialy clinically solitary angiokeratomas often resemble malignant melanoma in appearance. Solitary angiokeratoma is a rare disorder and its resemble malignant melanoma in appearance so we reported a case. ©2005, Fırat Üniversitesi, Tıp Fakültesi

Anjiokeratomlar subepidermal olarak yerleşen ve epidermal proliferatif reaksiyon gösteren, genişlemiş kan damarlarından oluşan vasküler lezyonlardır. Anjiokeratomlar benign lezyonlar olmasına rağmen özellikle soliter anjiokeratomlar klinik olarak malign melanom ile karıştırılabilirler. Soliter anjiokeratomun nadir görülmesi ve malign melanom ile benzerliğinin vurgulanması amacıyla olguyu sunmayı uygun bulduk. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Soliter Anjiokeratom Olgusu